Strategies for research engagement of clinicians in allied health (STRETCH): a mixed methods research protocol. Issue 9 (11th September 2017) - Mickan, Sharon; Wenke, Rachel; Weir, Kelly; Bialocerkowski, Andrea; Noble, Christy
Abstract : Introduction: Allied health professionals (AHPs) report positive attitudes to using research evidence in clinical practice, yet often lack time, confidence and skills to use, participate in and conduct research. A range of multifaceted strategies including education, mentoring and guidance have been implemented to increase AHPs' use of and participation in research. Emerging evidence suggests that knowledge brokering activities have the potential to support research engagement, but it is not clear which knowledge brokering strategies are most effective and in what contexts they work best to support and maintain clinicians' research engagement. Methods and analysis: This protocol describes an exploratory concurrent mixed methods study that is designed to understand how allied health research fellows use knowledge brokering strategies within tailored evidence-based interventions, to facilitate research engagement by allied health clinicians. Simultaneously, a realist approach will guide a systematic process evaluation of the research fellows' pattern of use of knowledge brokering strategies within each case study to build a programme theory explaining which knowledge brokering strategies work best, in what contexts and why. Learning and behavioural theories will inform this critical explanation. Ethics and dissemination: An explanation of how locally tailored evidence-based interventions improve AHPs use of, participation in and leadership of research projects will be summarised and shared with all participating clinicians and within each case study. It is expected that local recommendations will be developed and shared with medical and nursing professionals in and beyond the health service, to facilitate building research capacity in a systematic and effective way.